Woodland Wellbeing: a pilot for people with dementia. Issue 3 (11th September 2017) - Gibson, Elanor; Ramsden, Nicola; Tomlinson, Rachel; Jones, Charlie
Abstract : Purpose: The purpose of this paper is to understand whether a woodland-based intervention might offer something helpful and engaging for people affected by dementia. In total, 18 people came to Woodland Wellbeing groups over summer and autumn in 2016. Design/methodology/approach: The authors made observations during the groups, kept some notes and conducted some interviews around three months after people had participated in Woodland Wellbeing. Findings: Feedback from participants indicated themes around connection with nature and to one another; the joy in new learning and activities; and the inspirational impact of feeling part of nature. Originality/value: This paper adds to the growing literature on natural approaches in supporting the wellbeing of people affected by dementia, and highlights the value of partnership working.